A Suspicious Atypical Fracture of 5th Metatarsal Bone: A Case Report. Issue 4 (16th October 2019) - Park, Byeong-Seop; Koo, Seungbum; Park, Won-keun; Kwon, Ki-bum; Lee, Kyoung Min
Category: Trauma Introduction/Purpose: Long-term usage of bisphosphonate can severely suppress bone turnover and alter bone mechanical properties, thereby resulting in atypical fractures that mainly occur at the femur.We present a rare case of suspicious atypical fracture of the metatarsal bone. Methods: A 63-year-old woman presented to our clinic with a primary complain of a one-week history of pain in her right foot. The patient had no history of trauma to the right foot and denied any strenuous activity. She experienced lateral foot pain while walking within her home. She was on alendronate therapy for osteoporosis for a decade. X ray and CT examination revealed a fifth metatarsal fracture whose features were compatible with those of atypical femoral fractures (Figure 1). Results: The patient was advised to discontinue alendronate and underwent percutaneous surgical fixation of the fracture via a proximal approach using a 4.0-mm half-threaded cannulated screw. Postoperatively, a short leg cast was created and the patients performed non-weight bearing ambulation until the cast was removed at the sixth postoperative week. Radiography in the sixth postoperative week revealed callus formation. Conclusion: Our findings suggest that physicians must keep in mind that atypical fractures could possibly occur at bones other than the femur.